SEARCH FOR EXPERIMENTAL EVIDENCE OF DOSE-RATE AND WALL SCATTERING EFFECTS IN THE THERMOLUMINESCENCE RESPONSE OF LIF:MG, TI (TLD-100). Issue 4 (21st March 2022) - Ginzburg, Dimitry; Eliyahu, Ilan; Spooner, Nigel; Sterenberg, Matan; Reshes, Galina; Shapiro, Alex; Biderman, Shlomo; Herman, Beny; Assor, Yossi; Nemirovsky, Dimitry; Oster, Leonid; Horowitz, Yigal Shalom; et al.
Abstract: An experimental investigation into the possibility of dose-rate effects and wall scatter in the thermoluminescent response of LiF:Mg, Ti (TLD-100) was carried out. The investigation was motivated by theoretical simulations predicting the possible presence of dose-rate effects coupled with the lack of detailed experimental studies. The dose rate was varied by changing the source to sample distance, by the use of attenuators, sources of 137 Cs of various activities, filtration and the construction of identical geometrical irradiators of Teflon and stainless steel. Four levels of dose in the linear dose response region were studied at 10 −2 Gy, 1.5 × 10 −2 Gy, 0.1 Gy and 0.5 Gy to avoid complications in interpretation due to supralinearity above 1 Gy. At the dose of 1.5 × 10 −2 Gy, the dose rate was varied by five orders of magnitude from 4.9 × 10 −3 Gy s −1 to 4.9 × 10 −8 Gy s −1 . At the other levels of dose, a one to two orders of magnitude in dose rate was achieved. Within the measurement uncertainty of 5–10%, no dose-rate effects were observed in any of the experimental measurements and no changes in the shape of the glow curve were observed. The maximum wall scatter effect (Teflon to stainless steel) was measured at 8% within the experimental uncertainty and well below expectations. The results are encouraging with respect to the accurate and reproducible use of LiF:Mg, Ti under various experimental conditions of irradiation.